PENGARUH KEMUDAHAN, KEPERCAYAAN, DAN KEAMANAN TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN PADA TOKO ONLINE TOKOPEDIA - Nandya Eka Sari; Teddy Oswari (Creative Research Management Journal, 2020)
This study aims to determine the direct and indirect effects of convenience, trust and security oncustomer satisfaction through purchasing decisions on the Tokopedia online shop. The variablesused in this research are independent, intervening, and dependent variables. The independentvariables in this study are Ease ( ), Trust ( ), and Security ( ). The intervening variable inthis study is the Purchase Decision ( ). And the closest variable in this study is CustomerSatisfaction ( ). The sample was determined by purposive sampling technique. By distributingquestionnaires with a sample of 100 respondents. Then the data were processed using SPSS 24.0software to test the validity and reliability and to verify the answer to the research hypothesisusing the SmartPLS 3.0 software. The results of this study indicate that there is a significanteffect of convenience, trustworthiness, and security on purchasing decisions. There is asignificant effect of purchasing decisions on customer satisfaction. There is a significant effect ofconvenience and security on customer satisfaction, but the variable of trust has no effect oncustomer satisfaction. And there is no significant effect of convenience, trust, and security oncustomer satisfaction through purchasing decisions on the Tokopedia online shop .